The Mechanism and Clinical Significance of Circular RNAs in Hepatocellular Carcinoma - Huang, Ziyue; Xia, Haoming; Liu, Shuqiang; Zhao, Xudong; He, Risheng; Wang, Zhongrui; Shi, Wenguang; Chen, Wangming; Kang, Pengcheng; Su, Zhilei; Cui, Yunfu; Yam, Judy Wai Ping; et al. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors worldwide. In view of the lack of early obvious clinical symptoms and related early diagnostic biomarkers with high specificity and sensitivity, most HCC patients are already at the advanced stages at the time of diagnosis, and most of them are accompanied by distant metastasis. Furthermore, the unsatisfactory effect of the follow-up palliative care contributes to the poor overall survival of HCC patients. Therefore, it is urgent to identify effective early diagnosis and prognostic biomarkers and to explore novel therapeutic approaches to improve the prognosis of HCC patients. Circular RNA (CircRNA), a class of plentiful, stable, and highly conserved ncRNA subgroup with the covalent closed loop, is dysregulated in HCC. Increasingly, emerging evidence have confirmed that dysregulated circRNAs can regulate gene expression at the transcriptional or post-transcriptional level, mediating various malignant biological behaviors of HCC cells, including proliferation, invasion, metastasis, immune escape, stemness, and drug resistance, etc.; meanwhile, they are regarded as potential biomarkers for early diagnosis and prognostic evaluation of HCC. This article reviews the research progress of circRNAs in HCC, expounding the potential molecular mechanisms of dysregulated circRNAs in the carcinogenesis and development of HCC, and discusses those application prospects in the diagnosis and prognosis of HCC.